Exact Zoning Optimization Model for Marine Spatial Planning (MSP) - Basirati, Mohadese; Billot, Romain; Meyer, Patrick; Bocher, Erwan (Frontiers in Marine Science, 2021)
Marine spatial planning (MSP) has recently attracted more attention as an efficient decision support tool. MSP is a strategic and long-term process gathering multiple competing users of the ocean with the objective to simplify decisions regarding the sustainable use of marine resources. One of the challenges in MSP is to determine an optimal zone of a new activity while taking into account the locations of the other existing activities. Most approaches to spatial zoning are formulated as non-linear Multi-Objective models, which are usually solved using stochastic search algorithms, leading to sub-optimal solutions. In this paper, we propose to model the problem as a Multi-Objective Integer Linear Program (MOILP). The model is developed for raster data and it aims at maximizing the interest of the area of the zone dedicated to the new activity while maximizing its spatial compactness. We study two resolution methods: first, a weighted-sum of the two objectives, and second, an interactive approach based on an improved augmented version of the ε-constraint method, AUGMECON2. To validate and study the model, we perform experiments on artificially generated data. Our study shows also that AUGMECON2 represents the most promising approach in terms of relevance and diversity of the solutions, compactness, and computation time.